2008
DOI: 10.1136/bjo.2007.127738
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal keratocytes and stromal inflammation in chronic phase of severe ocular surface diseases with stem cell deficiency

Abstract: Background/Aims: Stevens-Johnson syndrome (SJS), ocular cicatricial pemphigoid (OCP) and alkali burns are associated with chronic, severe inflammation of the ocular surface that occasionally lead to corneal stem cell deficiencies. The corneal stroma in these diseases has not been studied comprehensively. The purpose of this study was to determine whether the keratocytes in the stroma were normal and whether the stroma remained inflamed in the chronic phase of these diseases. Methods: Five pathological corneas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…; Saito et al. ). Ocular surface infections can predispose to dry eye rather than the dry eye predisposing a patient to infections (Narayanan et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…; Saito et al. ). Ocular surface infections can predispose to dry eye rather than the dry eye predisposing a patient to infections (Narayanan et al.…”
Section: Discussionmentioning
confidence: 96%
“…Based on the evidence in the existing literature, there is insufficient evidence to strongly suggest that a typical dry eye patient will be at increased risk for microbial keratitis (Narayanan et al 2013). According to clinical observations, even in severe dry eye disorders, such as Sjögren's syndrome or ocular cicatricial pemphigoid, the corneal ulceration is sterile, but not infectious (Vivino et al 2001;Saito et al 2008). Ocular surface infections can predispose to dry eye rather than the dry eye predisposing a patient to infections (Narayanan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…8,19,[55][56][57][58] Upregulation of biglycan in aortic stenosis, characterized by lipid accumulation and inflammation, 59 results in enhanced synthesis of phospholipid transfer protein via stimulation of TLR2. 60 Furthermore, higher levels of biglycan in cardiac transplant coronary arteriopathy, 58 severe ocular surface disease 61 and in adipose tissue 62 suggest a role for biglycan in the perpetuation of inflammation. Further studies concerning the mechanisms of biglycan-driven inflammation in those pathophysiological processes would improve our understanding of how sterile inflammation is triggered.…”
Section: Decorin As Endogenous Ligand Of Tlr2/tlr4 and Tgfβ1 Inhibitomentioning
confidence: 99%
“…Saito and coworkers found that in severe ocular surface diseases such as SJS, OCP and alkali burn, the corneal stroma had persistent inflammation, even in the seemingly quiet phase, because the CD45-positive and CD14-positive cells were increased and the expression level of monocyte chemoattractant protein 1 (MCP1), macrophage inflammatory protein 1α (MIP 1α) and MIP1β were markedly high in all cornea 11. The chronic inflammation produces excessive collagenolytic activity and makes the tissue vulnerable to melting.…”
Section: Discussionmentioning
confidence: 99%